Culturing of female bladder bacteria reveals an interconnected urogenital microbiota - Krystal Thomas-White (Nature Portfolio, 2018)
The female bladder seems to harbor a poorly characterized indigenous microbiota. Here, the authors isolate and genome-sequence 149 bacterial strains from catheterized urine of 77 women, generating a culture collection representing two thirds of the bacterial diversity within the samples.